Transcriptomic analysis of the head reveals molecular mechanisms underlying topical imidacloprid effects on A. mellifera forager bees - de Castro Lippi, Isabella Cristina; Lima, Yan Souza [UNESP]; da Luz Scheffer, Jaine [UNESP]; Lunardi, Juliana Sartori [UNESP]; Kadri, Samir Moura [UNESP]; Alvarez, Marcus Vinícius Niz [UNESP]; de Oliveira Orsi, Ricardo [UNESP] (Springer Nature, 2025)
The global decline of bees has raised significant concerns due to their crucial role in agroecosystems, rendering their diminishment a potential predisposing factor for a worldwide crisis in the agri-food sector and ecosystems. The use of pesticides, such as neonicotinoids, can impact non-target organisms, including bees. This study aimed to evaluate the gene expression in the heads of Apis mellifera bees in the forager phase. The analysis was conducted by examining their transcriptome to assess the effects of the neonicotinoid imidacloprid through contact bioassays, administered at both lethal and sublethal doses. The results revealed differential gene expression after 1 and 4 h of imidacloprid exposure. Differentially expressed genes were categorized based on gene ontology, revealing alterations in critical biological processes, molecular functions, and cellular components. These changes were associated with immune response, stress, neurotoxicity, and other vital functions. The study highlights the importance of considering sublethal pesticide effects and their potential long-term consequences on bee populations and ecosystem functioning.
Keywords: beekeeping; genomic; honey bee; pesticide; transcriptome